2020
DOI: 10.30872/jlpf.v1i2.231
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Project Based Learning (PjBL) Untuk Meningkatkan Hasil Belajar Fisika Siswa Kelas XI SMA Negeri 5 Samarinda

Abstract: Project based Learning (PjBL) adalah model pembelajaran yang melibatkan siswa dalam kegiatan pembelajaran baik dalam merancang ataupun membuat proyek yang berguna untuk memecahkan permasalahan dalam kehidupan sehari-hari. Tujuan dari penelitian ini adalah untuk mengetahui peningkatan hasil belajar siswa setelah diterapkan model PjBL. Jenis  penelitian ini menggunakan penelitian kuantitatif dengan motode One Grup-Pretest-posttest. Teknik pengambilan sampel menggunakan purposive sampling dengan sampel yang digun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The PjBL model can train students to work independently or in groups in making and producing something. In addition, the Project Based Learning Model involves students in solving a problem and provides opportunities for students to express further their creativity which is expected to improve student learning outcomes (Nair & Suryan, 2020;Rante Datu et al, 2020;Surya et al, 2018). The PjBL model has been taught several times at SDN 1 Baktiseraga.…”
Section: Discussionmentioning
confidence: 99%
“…The PjBL model can train students to work independently or in groups in making and producing something. In addition, the Project Based Learning Model involves students in solving a problem and provides opportunities for students to express further their creativity which is expected to improve student learning outcomes (Nair & Suryan, 2020;Rante Datu et al, 2020;Surya et al, 2018). The PjBL model has been taught several times at SDN 1 Baktiseraga.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the Project-Based Learning (PjBL) model has been carried out by (Yance et al, 2013) that the physics learning outcomes of experimental classes that use Project Based Learning (PjBL) are higher than the physics learning outcomes of control classes that do not use PjBL. Another research conducted by (Datu et al, 2020) found that there was an increase in students' physics learning outcomes after using the Project-Based Learning (PjBL) learning model on Elasticity and Simple Harmonic Motion material. Further research conducted by (Wahyudi, 2021) stated that the application of the Project-Based Learning (PjBL) model could increase student learning outcomes in static electricity and dynamic electricity compared to other learning models.…”
Section: Introductionmentioning
confidence: 99%
“…This limits the ability of students to discover and try new things. In response to these problems, a project-based learning model is offered which can improve student learning outcomes (Datu, Qadar, & Junus, 2020). The PjBL model is a learning model that provides opportunities for teachers to manage learning in class by involving project work.…”
Section: Introductionmentioning
confidence: 99%